Elevational distribution patterns and drivers factors of fungal community diversity at different soil depths in the Abies georgei var. smithii forests on Sygera Mountains, southeastern Tibet, China - Zhang, Bo; Zhu, Sijie; Li, Jiangrong; Fu, Fangwei; Guo, Liangna; Li, Jieting; Zhang, Yibo; Liu, Yuzhuo; Chen, Ganggang; Zhang, Gengxin (Frontiers in Microbiology, 2024)
Introduction Soil fungal communities play a crucial role in maintaining the ecological functions of alpine forest soil ecosystems. However, it is currently unclear how the distribution patterns of fungal communities in different soil layers of alpine forests will change along the elevational gradients. Material and methods Therefore, Illumina MiSeq sequencing technology was employed to investigate fungal communities in three soil layers (0–10, 10–20, and 20–30 cm) along an elevational gradient (3500 m to 4300 m) at Sygera Mountains, located in Bayi District, Nyingchi City, Tibet. Results and discussion The results indicated that: 1) Soil depth had a greater impact on fungal diversity than elevation, demonstrating a significant reduction in fungal diversity with increased soil depth but showing no significant difference with elevation changes in all soil layers. Within the 0–10 cm soil layer, both Basidiomycota and Ascomycota co-dominate the microbial community. However, as the soil depth increases to 10–20 and 20–30 cm soil layers, the Basidiomycota predominantly dominates. 2) Deterministic processes were dominant in the assembly mechanism of the 0–10 cm fungal community and remained unchanged with increasing elevation. By contrast, the assembly mechanisms of the 10–20 and 20–30 cm fungal communities shifted from deterministic to stochastic processes as elevation increased. 3) The network complexity of the 0–10 cm fungal community gradually increased with elevation, while that of the 10–20 and 20–30 cm fungal communities exhibited a decreasing trend. Compared to the 0–10 cm soil layer, more changes in the relative abundance of fungal biomarkers occurred in the 10–20 and 20–30 cm soil layers, indicating that the fungal communities at these depths are more sensitive to climate changes. Among the key factors driving these alterations, soil temperature and moisture soil water content stood out as pivotal in shaping the assembly mechanisms and network complexity of fungal communities. This study contributes to the understanding of soil fungal community patterns and drivers along elevational gradients in alpine ecosystems and provides important scientific evidence for predicting the functional responses of soil microbial ecosystems in alpine forests.